Understanding and mitigating security and authentication issues in service oriented network architecture. (1st January 2015) - Rudra, Bhawana; Vyas, O.P.
Service oriented network architecture (SONATE) is one of the outcome of many architectures being explored to evolve as future network architecture. The architecture describes about the importance of flexibility to solve the short term as well as the long term requirements of the consumer (Manu et al., 2012; Rudra et al., 2011a). Flexibility is the solution for solving the architectural problems but raises many security problems. It is important to consider security must be considered as the integral part of design level rather than at the development stage of the architecture. This paper discusses various security requirements for the entities of the architecture and the importance of authentication. A public key based infrastructure (PKI) mechanism is proposed and discussed in detail.